ATM is associated with the prognosis of colorectal cancer: a systematic review - Wu, Pei; Wen, Zelin (Frontiers in Oncology, 2025)
ObjectiveChemosensitivity and radiosensitivity are associated with the prognosis of colorectal cancer, and the expression of the ataxia-telangiectasia mutated (ATM) protein plays an essential role in these processes. The present study examined the relationship between ATM expression and the survival outcomes of colorectal cancer patients and explored the underlying mechanism and promising therapeutic strategies.MethodA search including medical subject headings (MeSH), free terms, and combined words was conducted using Pubmed, EMBASE, and Cochrane. Studies had to meet the inclusion criteria as well as include processes such as data extraction and quality evaluation. The survival outcomes were assessed using hazard ratio (HR) and 95% confidence interval (CI). Heterogeneity, and publication bias were analyzed, and a P value <0.05 was considered statistically significant.ResultsNine studies with 2883 patients were included in the meta-analysis. Low ATM expression level was related to poor overall survival (HR=0.542, 95% CI=0.447–0.637; P=0.000). Disease-free, progression-free, and recurrence-free survival rates were lower in patients with low ATM expression than in those with high ATM expression. There was no significant difference between Stage I–II and Stage III–IV colorectal cancer patients [risk ratio (RR)=1.173, 95% CI=0.970–1.417, P=0.690].ConclusionsLow ATM expression level may be a marker of poor survival in colorectal cancer and contributes to resistance to therapy. Targeting related factors in these pathways to sensitize tumors to treatment is a potential therapeutic strategy, and monitoring ATM status could be a valuable guide independent of the immunotherapy or chemotherapy strategy used.